Hesperidin promotes gastric motility in rats with functional dyspepsia by regulating Drp1-mediated ICC mitophagy - Jia, Qingling; Li, Li; Wang, Xiangxiang; Wang, Yujiao; Jiang, Kailin; Yang, Keming; Cong, Jun; Cai, Gan; Ling, Jianghong (Frontiers in Pharmacology, 2022)
Hesperidin is one of the main active ingredients of Citrus aurantium L. (Rutaceae) and tangerine peel, which have anti-inflammatory and antioxidant effects. In previous study, we found that gastric motility disorder in functional dyspepsia (FD) rats accompanied by excessive autophagy/mitochondrial swelling and even vacuolization in the interstitial cells of cajal (ICC), but the exact mechanism has not yet been investigated. Therefore, we used different doses of hesperidin (50 mg/kg, 100 mg/kg, and 200 mg/kg) to intervene in FD rats, and found that medium doses of hesperidin (100 mg/kg) significantly increased gastric motility in FD rats. Subsequently, FD rats were randomly divided into control group, model group, mdivi-1 group, mdivi-1+hesperidin group and hesperidin group, and mitochondrial division inhibitor (mdivi-1) was injected intraperitoneally to further investigate whether hesperidin could regulate dynamin-related protein 1 (Drp1)-mediated mitophagy in ICC to improve mitochondrial damage. The results showed that compared with the model group, the serum malondialdehyde (MDA) level decreased and the superoxide dismutase (SOD) level increased in the mdivi-1 and hesperidin groups (P<0.001). Transmission electron microscopy (TEM) observed that the mitochondrial nuclear membrane was intact in gastric tissues with a clear internal cristae pattern, and autophagy lysosomes were rare. The co-localization expression of microtubule associated protein 1 light chain 3 (LC3) and voltage dependent anion channel 1 (VDAC1), Drp1 and translocase of the outer mitochondrial membrane 20 (Tom20) was significantly decreased (P<0.001), the protein expression of mitochondrial Drp1, Beclin1 and LC3 were significantly decreased (P<0.001), the protein expression of mitochondrial P62 and ckit in gastric tissue were significantly increased (P<0.05, P<0.001). The above situation was improved more significantly by the synergistic intervention of mdivi-1 and hesperidin. Therefore, hesperidin can improve mitochondrial damage and promote gastric motility in FD rats by regulating Drp1-mediated ICC mitophagy.